(untitled) (Journal of the College of Basic Education, 2022)
Waste in any educational system, whether due to repeated failure or because of dropping out Before completing the school stage, this is a clear indication of the inefficiency of the educational system. The economics of education is that the outputs are much less than the inputs, and this means that there is a loss from two aspects. The first is a waste of the money spent and the expended capabilities, and the second is a loss of resources. The society does not get all it needs from educated and trained human resources.